Political Participation, Upsurge in Youths’ Turnout for 2022 Continuous Voters’ Registration and Nigeria’s 2023 Electoral Process - AKELE, Oluwabanji A.; ARIYO, Ojo O.; AJAYI, Festus O. (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Political scientists and others involved in election administration have long been concerned about the importance of young people’s participation in politics, particularly in Africa. When it comes to politics, youth play an important role and are expected to play an even larger one through voter registration. Intriguingly, the youth of Nigeria showed remarkable eagerness to participate actively in the just finished 2023 electoral process by turning out in large numbers for the Continuous Voters’ Registration (CRV) drive in 2022. Examining the causes of the dramatic increase in young voters’ registration in Nigeria’s 2023 elections and the effects of this trend on youth participation in politics and the electoral process were the primary goals of this research. This study used a descriptive research strategy based on a survey design. Information was gathered by means of survey questionnaires and in-depth interviews. Tables and basic percentages were used for quantitative data analysis, while discourse analysis was used for analysing the content of qualitative data. The study’s results showed that the youths’ rights had been violated on a large scale, particularly in recent years. For instance, the handling of the 2020 End-SARS protest, such as being beaten with the butt of a gun, whips, and fists during arrest; continued torture by the police in detention, and the surge in support for Peter Obi were also factors that contributed to the surge. On the other hand, the implications of the massive turnout for governance and political participation in Nigeria include the youths’ ability to speak out against bad governance across ethno-religious lines, and an increase in youth participation in politics. The study concludes that young people should be more informed and engaged, that electoral institutions should be strengthened, and that voter registration should be continuous.